Development of immunoaffinity chromatography to specifically knockout baicalin from Gegenqinlian Decoction. Issue 15 (29th June 2015) - Zhao, Yan; Feng, Huibin; Shan, Wenchao; Cheng, Jinjun; Wang, Xueqian; Zhao, Yan; Qu, Huihua; Wang, Qingguo
<x xml:space="preserve">Abstract</x> Specific knockout technology provides a powerful tool to confirm the role of target compounds in a plant or its derived prescriptions, and this principle is the same as that with knockout genes. In this study, we generated an immunoaffinity column conjugated with an anti‐baicalin monoclonal antibody and then loaded Gegenqinlian Decoction extracts, followed by washing with deionized water and an elution solvent. The results of the high‐performance liquid chromatography fingerprints and high‐performance liquid chromatography with mass spectrometry showed that the immunoaffinity column was able to specifically knockout baicalin, oroxylin A‐7‐O‐glucuronide, wogonoside, wogonin, and baicalein from Gegenqinlian Decoction. A reliable one‐step method to specifically knockout baicalin was established with an immunoaffinity column. Gegenqinlian Decoction and its knocked‐out fraction induced the expression of superoxide dismutase and were compared in human umbilical vein endothelial cells cultured with a high glucose concentration; the results showed that the Gegenqinlian Decoction and its knocked‐out fraction showed no significant difference, which indicated that the baicalin, oroxylin A‐7‐O‐glucuronide, wogonoside, wogonin, and baicalein that were knocked out by the immunoaffinity column might not be key compounds for the induction of Gegenqinlian Decoction superoxide dismutase secretion.